2019
DOI: 10.1016/j.jcot.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term clinical outcome following rotator cuff repair using all-suture anchors

Abstract: Background: Symptomatic rotator cuff tears can cause significant pain and functional disturbance, with associated financial ramifications. Non-surgical management should always be considered initially, however if recalcitrant to these measures surgical intervention may involve open, arthroscopic-assisted mini-open or arthroscopic rotator cuff repairs. The use of trans-osseous sutures and suture anchors has been reported with good results, with no significant differences if the repair remains intact or recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…They found that only one patient sustained a retear and that there was no difference in the contralateral supraspinatus strength at mean postoperative 1.58 years [ 36 ]. Dhinsa et al analyzed 31 patients who underwent double-row repair and reported one retear at a mean follow-up of 10.2 months with a mean Constant score of 77.1 [ 11 ]. Ro et al retrospectively compared 213 patients who underwent single-row rotator cuff repair using all-suture ( n = 137), bioabsorbable ( n = 36) or PEEK anchors ( n = 40).…”
Section: Discussionmentioning
confidence: 99%
“…They found that only one patient sustained a retear and that there was no difference in the contralateral supraspinatus strength at mean postoperative 1.58 years [ 36 ]. Dhinsa et al analyzed 31 patients who underwent double-row repair and reported one retear at a mean follow-up of 10.2 months with a mean Constant score of 77.1 [ 11 ]. Ro et al retrospectively compared 213 patients who underwent single-row rotator cuff repair using all-suture ( n = 137), bioabsorbable ( n = 36) or PEEK anchors ( n = 40).…”
Section: Discussionmentioning
confidence: 99%
“…All-suture anchors were also tested, again in cadaveric studies, in tenodesis of the long head of the biceps, with encouraging results [ 18 ]. In a single study, the functional outcome was assessed by means of constant on a small number of patients, without however a radiological evaluation or a comparison with a similar system used by the same surgeon [ 19 ]. It is fair to say that the literature does not provide reliable clinical or instrumental parameters for the prognosis of arthroscopic repair, thus highlighting poor reproducibility of the evaluation indices considered [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, shoulder healing after surgery is of great interest to determine which surgical repair techniques are the best for tendon repair [39] or to maintain its integrity [40]. Furthermore, it is important to determine the effect of post-surgical rehabilitation [4143], and current research is focused on clinical outcomes including both PRO and ROM [44, 45]. In this regard, future studies with a wider sample should include sensitivity and specificity assessment in order to determine its value as a diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%